Q:

Find a cubic function with the given zeros. Square root of two., - Square root of two., -2 f(x) = x3 + 2x2 - 2x + 4 f(x) = x3 + 2x2 + 2x - 4 f(x) = x3 - 2x2 - 2x - 4 f(x) = x3 + 2x2 - 2x - 4\",[{""content"":""<p><strong>Answer:<\/strong><\/p><p>f(x) = x^3 + 2x^2 - 2x - 4<\/p><p><strong>Step-by-step explanation:<\/strong><\/p><p>Hi!<\/p><p><\/p><p>We \u00a0only need to multiply the following monomials:<\/p><p>(x - \u221a2)<\/p><p>(x + \u221a2)<\/p><p>(x + 2)<\/p><p><\/p><p>Since each of them has a zero in the required values.<\/p><p>Therefore:<\/p><p>(x - \u221a2)*(x + \u221a2)*(x + 2) = (x + 2)*(x^2 - 2)<\/p><p><u><em>*Here I have used the property:<\/em><\/u><\/p><p><u><em>(x-a)*(x+a) = x^2-a^2 <\/em><\/u><\/p><p><u><em>*with a = \u221a2<\/em><\/u><\/p><p>(x - \u221a2)*(x + \u221a2)*(x + 2) = (x + 2)*(x^2 - 2) = x^3 -2x + 2x^2 - 4<\/p><p><\/p><p>That is:<\/p><p>f(x) = x^3 + 2x^2 - 2x - 4<\/p><p>The correct answer is the third<\/p>""}

Accepted Solution

A:
{""content"":""Answer is:
x = 0